2022
DOI: 10.38053/acmj.1062754
|View full text |Cite
|
Sign up to set email alerts
|

Rubella, cytomegalovirus and toxoplasmosis seroprevalence in pregnants in Çorum Province

Abstract: Aim: Toxoplasma gondii (T. gondii), rubella virus and cytomegalovirus (CMV) are important factors that can be transmitted from mother to baby and cause clinical findings in fetus or newborn. In our study, it was aimed to determine the seroprevalence of T. gondii, rubella virus and cytomegalovirus in pregnant women who applied to our hospital. Material and Method: In our study, the serological test results of the blood samples of pregnant women used in the diagnosis of T. gondii, rubella virus and CMV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…In contrast, other researchers indicated that autistic cases had a significantly higher rate of CMV prevalence than healthy children (Kawashti et al 2006 ; Engman et al 2015 ; Sakamoto et al 2015 ). In the current study, CMV showed a high prevalence in both autistic and control groups, which conforms with previous reports suggesting a high prevalence of CMV seropositivity, especially in developing countries (Lachmann et al 2018 ; Arapović et al 2020 ; Kahraman and Savcı 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, other researchers indicated that autistic cases had a significantly higher rate of CMV prevalence than healthy children (Kawashti et al 2006 ; Engman et al 2015 ; Sakamoto et al 2015 ). In the current study, CMV showed a high prevalence in both autistic and control groups, which conforms with previous reports suggesting a high prevalence of CMV seropositivity, especially in developing countries (Lachmann et al 2018 ; Arapović et al 2020 ; Kahraman and Savcı 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, both autistic and control children showed significantly higher CMV incidence than toxoplasmosis, which conforms to the reports of Mahic et al ( 2017 ), Frye et al ( 2019 ), and Kahraman and Savcı ( 2022 ). Despite the absence of any significant difference in the prevalence of Toxoplasma or CMV between the autistic and control groups, the autistic children documented a higher risk of infection than the control, which can be explained by the association with immune abnormalities in autistic children compared to the healthy ones, as reported previously (Raouf et al 2022 ).…”
Section: Discussionsupporting
confidence: 90%